Monitoring COVID-19 Impacts on Firms in Ethiopia, Report No. 8 : Results from a High-Frequency Phone Survey of Firms - Bundervoet, Tom; Abebe, Girum; Wieser, Christina (World Bank, Washington, DC, 2020)
This one-pager summarizes the results of the sixth round of the HFPS-F in Addis Ababa, implemented between August 17 and September 8, 2020. The information presented here is based on 331 firms that were still operational at the time of the survey. Firms that had temporarily closed because of the COVID pandemic were not interviewed in R6, which is a difference with the previous survey rounds (when temporarily closed firms were also interviewed). Firm closures will be looked at in detail in a separate brief.